Nonverbal communication: about the sound of the speech (for example, Russian and Kazakh languages). (Eurasian Journal of Philology Science and Education, 2015)
During the process of conversing of different cultures’ representatives in the public sphere the interest in the study of national and cultural specificity of intercultural communication has increased significantly. Specific features in communication are shown not only on verbal level, but also they are reflected on the non-verbal level. Different people use various nonverbal means as symbolic elements. The values of these non-verbal means are caused by certain environment, so representatives of various nations differ from each other by the picture of mimic behavior and character of gestures that allows to talk about their national character and connected with the ethnic, geographic and socio-cultural environment. Nonverbal behavior of the Kazakh people has its own unique features, which reflect the specifics of the national character, national consciousness, mentality, culture and life. Known that "sound speech includes two interrelated aspects: acoustic which is manifested in speech reproduction and perceptual which is appeared in the perception of speech." Acoustic aspect of communication is one of the components of non-verbal behavior.
Keywords: non-verbal behavior; intercultural communication; mentality; national specifics; gestures; facial expressions; speech audio side; the pace and tone